Sprünge einer neuen Generation - Beobachtungen und Entwicklungen im Elite Dreisprung der Männer - Niessen, M.; Jürgens, A.; Hartmann, U. (Leipziger Sportwissenschaftliche Beiträge, 2016)
During the last 20 years there were a total of 10 regular jumps beyond 18 m in elite male triple jumping (TJ), five of them by two triple jumpers in 2015 alone. With 18.21 m C. Taylor (USA) scored the second-best ever-achieved distance behind J. Edwards` (GBR) world record (WR) jump of 18.29 m. The aim of this report is to reveal and explain observations and developments on motion techniques, training philosophies and jumping styles of the world's best 18 m TJ. In addition a classification of German national elite TJ will be given followed by expectations and requirements for specific training and finally recommendations for further research will be made.